Double-Masked and Unmasked Prospective Study of Terpinen-4-ol Lid Scrubs With Microblepharoexfoliation for the Treatment of Demodex Blepharitis. Issue 4 (April 2020) - Epstein, Ilan J.; Rosenberg, Eric; Stuber, Ross; Choi, Michael B.; Donnenfeld, Eric D.; Perry, Henry D.
Abstract : Purpose: To evaluate terpinen-4-ol lid scrubs (Cliradex) with Microblepharoexfoliation (MBE) (BlephEx) in the treatment of Demodex blepharitis. Methods: An Institutional Review Board (IRB) approved the randomized prospective double-masked trial of 50 patients with Demodex positive blepharitis. All subjects were given an in-office MBE treatment and randomized to masked lid scrubs (terpinen-4-ol or sham) twice daily for 1 month. All subjects then returned for an additional MBE treatment and received open-label terpinen-4-ol scrubs twice daily for 1 month. Outcomes: Demodex levels, Ocular Surface Disease Index, tear osmolarity, MMP-9, Schirmer 1 and grading of the lid margin appearance, meibomian gland dropout, and meibomian gland secretions. Results: Forty-six subjects (23 per group) were included for the analysis; 4 lost to follow up. Total Demodex folliculorum levels in the Cliradex group improved: 4.7 to 3.6 (first month interval P = 0.266) to 2.6 (second month interval P = 0.279), overall P < 0.05 over 2 months. Total levels in the sham group improved: 5.1 to 3.0 (first month interval P < 0.05) to 2.5 (second month interval P = 0.496), overall P < 0.05 over 2 months. No clear statistically meaningful improvements in other dry eye and blepharitis data metrics were observed. Conclusions: In-office MBE treatments combined with either Cliradex terpinen-4-ol medicated lid scrubs or sham scrubs showed a statistically significant reduction in D. folliculorum infestation levels; however, conclusions on clinical significance could not be made. In-office MBE with terpinen-4-ol lid scrubs showed no significant improvement over sham scrubs.